2020
DOI: 10.1155/2020/9097426
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Research on the Load Transfer Mechanism of Anchoring System in Soft and Hard Composite Rock Strata under Tensile Loading Conditions

Abstract: Soft and hard composite rock strata are frequently encountered in transportation, geotechnical, and underground engineering. However, most of the current support is designed for homogeneous rock masses, which ignores the different anchoring effect in soft and hard composite rock strata. A numerical study is presented in this paper on the pull-out behavior of fully grouted rock bolts in soft and hard composite rock strata. The nonlinear bond-slip relationship of bolt-grout interface that is anchored in soft roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that bonded bolts in different rocks have different shear strength parameters of the anchorage interface. 47,48 In coal mines, the layered rock mass structure are composed of different types of rocks, such as hard rock and soft rock. Therefore, to investigate the pullout bearing performance of fully grouted bolts in layered rock mass, hard rock and soft rock were set up in the layered rock mass, and different shear strength parameters of the anchorage interface were used to simulate the interface mechanical behavior of fully grouted bolts in hard rock and soft rock, as shown in Figure 5.…”
Section: Bond-slip Relationship Of Anchorage Interface In Different R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that bonded bolts in different rocks have different shear strength parameters of the anchorage interface. 47,48 In coal mines, the layered rock mass structure are composed of different types of rocks, such as hard rock and soft rock. Therefore, to investigate the pullout bearing performance of fully grouted bolts in layered rock mass, hard rock and soft rock were set up in the layered rock mass, and different shear strength parameters of the anchorage interface were used to simulate the interface mechanical behavior of fully grouted bolts in hard rock and soft rock, as shown in Figure 5.…”
Section: Bond-slip Relationship Of Anchorage Interface In Different R...mentioning
confidence: 99%
“…According to the bearing mechanism of the bonded anchorage system, the shear strength parameters of the anchorage interface determine the bearing performance of fully grouted bolts. Previous studies have shown that bonded bolts in different rocks have different shear strength parameters of the anchorage interface 47,48 . In coal mines, the layered rock mass structure are composed of different types of rocks, such as hard rock and soft rock.…”
Section: Mechanical Behavior Of Anchorage Interface and Its Realizationmentioning
confidence: 99%
“…This model is rewritten and implemented as a subroutine by FISH language in Flac3D Version 5.0. Then, the nonlinear bond slip relationship is putting into the numerical simulation model by user-defined cs_cstable for expressing the nonlinear characteristics of the anchoring interface [27,29].…”
Section: Study On Stressmentioning
confidence: 99%
“…After unloading, the deformation of the structure cannot be completely recovered and there will be residual deformation and energy dissipation. According to "The technical specification for concrete structures of tall buildings," the energy dissipation capacity of specimens should be measured by the area enclosed by the load-displacement curve [11][12][13][14]. Figure 5 is a schematic diagram for calculating the energy dissipation and equivalent viscous damping coefficients of specimens.…”
Section: Structural Systemmentioning
confidence: 99%